Nutritional perfomance of Tupinambis merianae lizards fed with corn starch as source of energy - Vega Parry, Harold Enrique Bernabé (2009)
Efficiency in processing complex carbohydrates as a source of energy was studied in Tupinambis merianae lizards. Four isoproteic and isoenergetic diets in which different percentages of corn starch substituted fat (0, 10, 20 and 30 dry matter in the diet) were provided. Even though consumption was similar in all diets, growth and feeding conversion rates decreased significantly with corn starch supplies of 10% and more. At the end of the trial, pancreatic alpha-amylase activity showed correlated increases, yet these were insufficient to compensate corn starch supplies. Results suggest that Tupinambis merianae lizards have a restricted omnivorous capacity. Therefore, diet formulation for these lizards should exclude high molecular weight carbohydrates.